Low-molecular-weight heparin adherence and effects on survival within a randomised phase III lung cancer trial (RASTEN). (September 2019) - Gezelius, E.; Bendahl, P.O.; Gonçalves de Oliveira, K.; Ek, L.; Bergman, B.; Sundberg, J.; Strandberg, K.; Krämer, R.; Belting, M.
Abstract: Background: Coagulation activation is a hallmark of cancer, and anticoagulants have shown tumour-inhibiting properties. However, recent trials have failed to demonstrate improved survival with low-molecular-weight heparin (LMWH) in cancer populations. This has raised the question of suboptimal adherence as a possible explanation for the lack of benefit. Still, there is no standardised method to directly monitor LMWH in patient plasma. Here, we directly determine LMWH levels in patients using the Heparin Red assay to objectively assess adherence and how this associates with the patient outcome in the RASTEN trial. Methods: RASTEN is a multicentre, randomised phase III trial investigating if the addition of LMWH to standard therapy can improve survival in small-cell lung cancer. LMWH was measured in plasma ( N = 258) by the Heparin Red assay and compared with the anti–factor Xa (anti-FXa) activity assay. Results: Both methods could differentiate patients in the LMWH arm from the control arm and patients receiving therapeutic LMWH owing to thrombosis. Receiver Operating Characteristic (ROC) analysis yielded adherence rates of 85% for anti-FXa and 68% for Heparin Red. No survival benefits were found in the adherent subgroup compared with the control arm (hazard ratio [HR]: 1.26; 95% confidence interval [CI]: 0.95–1.67; P = 0.105 and HR: 1.19; 95% CI: 0.89–1.60; P = 0.248 for anti-FXa and Heparin Red, respectively). Heparin Red could define patients with high probability of adherence to LMWH treatment, which warrants prospective studies for further validation. Our finding that the LMWH-adherent subpopulation did not show improved survival excludes that the negative outcome of RASTEN was due to poor adherence. Highlights: Tumour-inhibiting effects by anticoagulants have been proposed. Suboptimal adherence to low-molecular-weight heparin may affect survival. For the first time, adherence has been assessed objectively using two assays. We found that adherence to low-molecular-weight heparin does not improve survival. General anticoagulant therapy is not recommended in lung cancer treatment.